Behavioral Intention of Receiving Monkeypox Vaccination and Undergoing Monkeypox Testing and the Associated Factors Among Young Men Who Have Sex With Men in China: Large Cross-Sectional Study - Sitong Luo; Kedi Jiao; Yuhang Zhang; Yutong Xu; Jingtao Zhou; Siwen Huang; Yan Li; Yongkang Xiao; Wei Ma; Lin He; Xianlong Ren; Zhen Dai; et al. (JMIR Publications, 2024)
BackgroundThe worldwide human monkeypox (mpox) outbreak in 2022 mainly affected men who have sex with men (MSM). In China, young men who have sex with men (YMSM) were at a potential high risk of mpox infection due to their sexual activeness and the eased COVID-19 restrictions at the end of 2022. ObjectiveThis study aimed to investigate the behavioral intention of receiving mpox vaccination and undergoing mpox testing in 4 different scenarios and explore their associations with background and behavioral theory-related factors among Chinese YMSM. MethodsAn online cross-sectional survey was conducted among YMSM aged 18-29 years from 6 representative provinces of China in September 2022. Participants recruited (recruitment rate=2918/4342, 67.2%) were asked to self-administer an anonymous questionnaire designed based on prior knowledge about mpox and classic health behavior theories. Data on the participants' background, mpox knowledge and cognition, mpox vaccination and testing cognition, and the behavioral intention of receiving mpox vaccination and undergoing mpox testing were collected. Descriptive analysis and univariate and multivariate linear regressions were performed. Geodetector was used to measure the stratified heterogeneity of behavioral intention. ResultsA total of 2493 YMSM with a mean age of 24.6 (SD 2.9) years were included. The prevalence of having a behavioral intention of receiving mpox vaccination ranged from 66.2% to 88.4% by scenario, varying in epidemic status and cost. The prevalence of having an mpox testing intention was above 90% in all scenarios regardless of the presence of symptoms and the cost. The positive factors related to vaccination intention included mpox knowledge (ba=0.060, 95% CI 0.016-0.103), perceived susceptibility of mpox (ba=0.091, 95% CI 0.035-0.146), perceived severity of mpox (ba=0.230, 95% CI 0.164-0.296), emotional distress caused by mpox (ba=0.270, 95% CI 0.160-0.380), perceived benefits of mpox vaccination (ba=0.455, 95% CI 0.411-0.498), self-efficacy of mpox vaccination (ba=0.586, 95% CI 0.504-0.668), and having 1 male sex partner (ba=0.452, 95% CI 0.098-0.806), while the negative factor was perceived barriers to vaccination (ba=-0.056, 95% CI -0.090 to -0.022). The positive factors related to testing intention were perceived severity of mpox (ba=0.283, 95% CI 0.241-0.325), perceived benefits of mpox testing (ba=0.679, 95% CI 0.636-0.721), self-efficacy of mpox testing (ba=0.195, 95% CI 0.146-0.245), having 1 male sex partner (ba=0.290, 95% CI 0.070-0.510), and having in-person gatherings with MSM (ba=0.219, 95% CI 0.072-0.366), while the negative factor was emotional distress caused by mpox (ba=-0.069, 95% CI -0.137 to -0.001). ConclusionsAmong Chinese YMSM, the intention of undergoing mpox testing is optimal, while the mpox vaccination intention has room for improvement. A future national response should raise YMSM's mpox knowledge, disseminate updated information about mpox and preventive measures, improve preventive service accessibility and privacy, and provide advice on positively coping with the associated emotional distress.